The Stone Age of Indonesia - van Heekeren, H. (0445e784-25b7-47fb-bca6-02216af224c0, 1972)
The first edition of The Stone Age of Indonesia was published as Volume 21 (1957) in the series Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde.